Effect of Infant Massage on Sleep Quality Of Baby 3-6 Months - Dewi Taurisiawati Rahayu (Journal of Applied Nursing and Health, 2022)
Background: One of the problems experienced by babies is poor sleep quality. This study aims to determine the description of sleep quality in infants who received infant massages. The purpose of this research was to Description Of Sleep Quality Of Babies Aged 3-6 Months After Infant Massage In Pmb Lilis Suryawati, Jombang   Regency Methods: The design used is descriptive. The population in this study was 54 infants aged 3-6 months, and a sample size of 36 was obtained. The sampling technique used was purposive sampling. The instrument used was a questionnaire about sleep quality. Infant massage is a routine procedure used at the research site, namely PMB Lilis Suryawati Jombang. This study was conducted on July 7 – August 29, 2021. Results: The results of this study indicate that the sleep quality of infants who were massaged almost entirely (52.8%) had good sleep quality. Baby massage relaxes baby's body muscles and improves sleep quality. Conclusion: Education to get Good sleep quality in Baby massage relaxes baby's body muscles and can improve sleep quality.